Digital-based adolescent health information literacy at SMP Negeri 19 Tanjung Jabung Timur - Nurlinwati Nurlinwati; Kamariyah Kamariyah; Yuliana Yuliana; Indah Mawarti (Community Empowerment, 2024)
Improving adolescent digital literacy is very important considering the rampant misuse of the internet. This community service activity aimed to improve the knowledge of grade IX students of SMPN 19 Tanjung Jabung Timur about digital-based adolescent health information. Community service activities were carried out through lectures, practices, demonstrations, and pre-test and post-test evaluations. The results of this activity showed a significant increase in students' understanding of the definition of literacy (100%), forms of literacy (80%), benefits of literacy (86%), sources of digital literacy (93%), types of digital media (96%), and adolescent health problems (70%). Thus, it is hoped that students can be wiser in utilizing digital technology and avoid its negative impacts.